Profil Pohon pada jenis Litsea spp. di Hutan Pendidikan - Fajriansyah, Fajriansyah; Diana, Rita; Matius, Paulus (MAKILA, 2019)
The purpose of this study was to determine the morphological condition of Litsea spp. Including the condition of the trunk, branching, the canopy, especially the relationship between the diameter of the trunk and the total height of the tree, the diameter of the trunk to the width of the canopy, and the total height of the tree to the width of the canopy in the Education Forest, Faculty of Forestry, Mulawarman University Samarinda East Kalimantan. The method of this study was purposive sampling method, which looking for Litsea spp. As the object of research as many as 33 trees and seven types of Litsea spp. The tree parameters measured were diameter, branch free, tree height, and canopy width. The results showed that 57.4% of the trees were healthy. The results of the tree's overall data analysis showed that the regression coefficient value between diameter and height, and diameter with canopy width have a moderate correlation value, this indicated that the diameter of the tree has no relationship to tree height and canopy width in Litsea spp. And similar conditions also occurred in the correlation between the height of the tree, which also has a moderate correlation, so it indicated the tree's height does not affect the width of the canopy